2018
DOI: 10.1111/gcb.14283
|View full text |Cite
|
Sign up to set email alerts
|

Spring photosynthetic onset and net CO2 uptake in Alaska triggered by landscape thawing

Abstract: The springtime transition to regional-scale onset of photosynthesis and net ecosystem carbon uptake in boreal and tundra ecosystems are linked to the soil freeze-thaw state. We present evidence from diagnostic and inversion models constrained by satellite fluorescence and airborne CO from 2012 to 2014 indicating the timing and magnitude of spring carbon uptake in Alaska correlates with landscape thaw and ecoregion. Landscape thaw in boreal forests typically occurs in late April (DOY 111 ± 7) with a 29 ± 6 day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
60
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 102 publications
(180 reference statements)
11
60
1
Order By: Relevance
“…Solar-induced chlorophyll fluorescence (SIF) is an electromagnetic signal emitted by plants during foliar light absorption by chlorophyll (Joiner et al, 2013;van der Tol, Berry, Campbell, & Rascher, 2014). SIF is directly proportional to photosynthetic activity (Porcar-Castell et al, 2014) and was shown to be an important indicator of photosynthetic activation and growing season duration throughout northern latitude ecosystems (Jeong et al, 2018;Parazoo et al, 2018). Spaceborne SIF is less sensitive to clouds, high albedo surfaces, and non-photosynthetic vegetation than reflectance-based vegetation indices.…”
Section: Gome-sifmentioning
confidence: 99%
See 2 more Smart Citations
“…Solar-induced chlorophyll fluorescence (SIF) is an electromagnetic signal emitted by plants during foliar light absorption by chlorophyll (Joiner et al, 2013;van der Tol, Berry, Campbell, & Rascher, 2014). SIF is directly proportional to photosynthetic activity (Porcar-Castell et al, 2014) and was shown to be an important indicator of photosynthetic activation and growing season duration throughout northern latitude ecosystems (Jeong et al, 2018;Parazoo et al, 2018). Spaceborne SIF is less sensitive to clouds, high albedo surfaces, and non-photosynthetic vegetation than reflectance-based vegetation indices.…”
Section: Gome-sifmentioning
confidence: 99%
“…The net CO 2 exchange depends on the balance between CO 2 assimilation through vegetation productivity and CO 2 release through ecosystem respiration (ER), which may respond differently to seasonal climate and environmental variations. High‐latitude ecosystems are generally temperature or radiation limited, and therefore, warming has a primary control on the seasonal change in photosynthesis or respiration (Parazoo et al, ; Figure ). Climate warming promotes earlier landscape thawing, a reduction in spring snow cover, earlier onset of vegetation productivity, and longer growing seasons (Box et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean annual temperature and precipitation are −8.28 °C and 304 mm, respectively. Mean July maximum daily temperature is ∼12 °C, and mean summertime precipitation is 210 mm (Parazoo et al, ; Riedel et al, ). Half‐hourly data from years 2004–2007 were made available through the FLUXNET network (Zona & Oechel, ).…”
Section: Methodsmentioning
confidence: 99%
“…GPP MAX ; figure 1). We also define the GPP onset date as the mean DOY when GPP is between 10% and 20% of GPP MAX for that year (Parazoo et al 2018). This definition can account for observation noise and range of transition dates from slow to rapid spring recovery in arctic tundra and boreal ecosystems.…”
Section: The Definition Of Budburst Start and Gpp Onsetmentioning
confidence: 99%